Syngonanthus nitens (Bong.) Ruhland: caracterização biológica e prospecção terapêutica do extrato metanólico incorporado ou não em sistema nanoestruturado para aplicação no tratamento da candidíase vulvovaginal - Ramos, Matheus Aparecido dos Santos [UNESP] (2015)
The indiscriminate and widespread use of antifungal drugs with potential led to a rapid development of resistant strains to drugs used in clinical, therapeutic and this is characterized as the main cause of numerous cases of inappropriate patient to drug therapy available. Natural products have been gaining prominence in recent years for providing a new drug therapy for the treatment of pathological processes, among these, infectious. During the genetic and physiological evolution of micro-organisms, microbiological sciences are expanding, worrying to introduce new therapeutic trials ahead to fungal diseases, with special attention to those acquired by Candida species, this being one of yeasts more often involved in mycotic infections can cause harm to human body, such as vulvovaginal candidiasis. The use of natural products in the discovery of new antifungal is extremely important, the example, is the Syngonanthus nitens species (gold grass) that has proved active in the discovery of antifungal potential against Candida spp. The pharmaceutical nanotechnology presents itself as an important tool to improve the bioavailability of natural product origin, offering modern drug release systems as precursors of mucoadhesive liquid crystal systems (PMLCS) employees for placement of plant extracts. The plants belonging to family Eriocaulaceae show promise in antifungal activity, which encourages the deepening of these investigations, as well as the discovery of new methods of applicability. Front of the current scenario, this work aimed to evaluate the antifungal potential of the methanol extract of Syngonanthus nitens scapes incorporated and not incorporated in PMLCS focusing on the treatment of vulvovaginal candidiasis. The study was conducted by applying in vitro and in vivo antifungal methods intended to elucidate the profile, having obtained satisfactory results as regards the applicability thereof in the treatment and prevention of VVC. The ...